ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL, DIVIDEND PAYOUT RATIO, TANGIBILITY, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 - 2015 - Setiawati, Loh Wenny; Raymond, Richardson (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
Peraturan Pemerintah (PP) Nomor 1 Tahun 2017 which has been officially legalized by the Government of Indonesia in effort to encourage the establishment of smelter facilities in the country have an impact on mining companies, especially on the company's debt policy. This research aims to study the effect of institutional ownership, dividend payout ratio, tangibility, and firm size on company debt policy as measured by debt ratio. This research uses multiple linear regression analysis with secondary data in the form of annual reports and audited financial statement from mining sector companies listed on the Indonesia Stock Exchange in 2013-2015 period. From total population of 43 companies in the mining sector, 32 companies were selected to be the sample of this research with a total of 96 observations in 3 years. The results of this research indicate that from the four independent variables tested, institutional ownership and dividend payout ratio has an influence on debt policy, while tangibility and firm size have no influence on debt policy.